The Effect of Using Children's Storybooks on Early Reading Skills in First Grade Students of Mis Al-Ikhlasiyah - Riris Tambunan, Novalia; Rosmawati Harahap (International Journal of Educational Research Excellence (IJERE), 2026)
In accordance with the formulation of the problem, this study aimed to determine the effect of the use of children's story books on the early reading skills of first-grade students at Mis Al-Ikhlasiyah. This study used a quantitative pre-experiment method with a two-group pretest-posttest. The research subjects consisted of two groups of first-grade students: an experimental group (N = 27) and a control group (N = 27). In this study, the subjects were first given a pre-test to determine their initial abilities before being taught using storybooks. Following the pretest, the students were given treatment, namely storybooks. After completion, the students were given a posttest to determine the extent of the storybook’s influence on their reading ability. The Effect of Children's Storybook Media: The use of children's storybooks significantly improves the early reading skills of first-grade students in MIS Al-Ikhlasiyah. This is evident from the increase in the average score of students in the experimental class (pretest 70.44 to posttest: 80.3) and the percentage of completion (48.15% to 85%). Differences between the Experimental and Control Classes: The control class also experienced improvement but was not as significant as the experimental class. The completion rate of the control class was only 33%, compared to 85% in the experimental class. Effectiveness of Children's Storybook Media: Children's storybook media have been proven to be effective in increasing students' interest and early reading skills compared to conventional methods.